2014
DOI: 10.5603/ep.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

Przydatność oznaczania stężenia PTH w popłuczynach z igły do biopsji aspiracyjnej cienkoigłowej w identyfikowaniu patologicznych przytarczyc — analiza czynników wpływających na skuteczność tej metody

Abstract: Usefulness of PTH measurements in FNAB washouts in the identification of pathological parathyroids -analysis of the factors that influence the effectiveness of this methodPrzydatność oznaczania stężenia PTH w popłuczynach z igły do biopsji aspiracyjnej cienkoigłowej w identyfikowaniu patologicznych przytarczyc -analiza czynników wpływających na skuteczność tej metody AbstractIntroduction: The aim of this investigation was to assess the usefulness of the measurement of PTH concentration in the material obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Maser et al proposed that a PTH level above the normal reference laboratory range was sufficient for diagnosis (18), while Abdelghani et al proposed that the PTH level in washout fluid should be higher than the serum level (20). When small volumes (0.5 or 1 mL) of saline usage for rinsing of the aspirates are taken into account, it can be assumed that the level would be at least 10-20 times lower than the exact value (21). However, in most of the studies PTH levels of washout were hundreds and thousands of times greater than serum PTH levels (3,19,22).…”
Section: Discussionmentioning
confidence: 99%
“…Maser et al proposed that a PTH level above the normal reference laboratory range was sufficient for diagnosis (18), while Abdelghani et al proposed that the PTH level in washout fluid should be higher than the serum level (20). When small volumes (0.5 or 1 mL) of saline usage for rinsing of the aspirates are taken into account, it can be assumed that the level would be at least 10-20 times lower than the exact value (21). However, in most of the studies PTH levels of washout were hundreds and thousands of times greater than serum PTH levels (3,19,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, in certain circumstances, the need to further identify the culprit gland, including measurement of high PTH in a lesion suspected as a parathyroid adenoma, becomes relevant. These circumstances include discordant imaging findings, 3–5 challenging anatomy (multinodular goiter or concomitant Hashimoto's thyroiditis), 6–8 intrathyroid adenoma, 9 and a history of neck surgery 5 …”
Section: Introductionmentioning
confidence: 99%
“…These circumstances include discordant imaging findings, [3][4][5] challenging anatomy (multinodular goiter or concomitant Hashimoto's thyroiditis), [6][7][8] intrathyroid adenoma, 9 and a history of neck surgery. 5 A number of studies showed excellent sensitivity (up to 95%) and positive predictive value (PPV, up to 100%) of PTH washout [10][11][12][13][14][15] ; and provided reassurance regarding the immediate safety of the procedure.…”
mentioning
confidence: 99%